The effects of the ZnO nanoparticles buffer layer on organic solar cells - Mbule, Pontsho Sylvia (University of the Free State, 2013)
Organic photovoltaics devices have drawn a lot of attention as means for the renewable energy conversion due to the remarkable combination prospective low cost of manufacturing and rapid improvement of performance approaching the traditional silicon solar cells. By introducing metal oxides in organic photovoltaics, the organic solar cells show great potential in terms of device performance with high exciton dissociation, the favorable charge transport ability and the air stability. In this study, ZnO nanostructures are investigated as a buffer layer in organic solar cells (OSCs), focusing on their impact on the device performance. ZnO nanoparticles, nanoflakes and nanoflowers were successfully synthesized using a wet chemistry route. Based on X-ray diffraction (XRD), the ZnO nanopaticles, nanoflakes and nanoflowers exhibited a hexagonal wurtzite structure matching the standard JCPDS data, card number 80-0075. The particle morphology of ZnO nanostructures was analyzed using field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). SEM revealed spherical nanoparticles, randomly oriented nanoflakes and nanoflowers clusters. TEM revealed nanorods clustered into nanoflowers. UV-visible absorption spectra of ZnO nanostructures exhibited peaks at ~251 nm and ~348 nm, attributed to structural defects and intrinsic excitons, respectively. Conventional and inverted organic solar cells were successfully fabricated. The fabrication process of conventional solar cells was optimized by varying several important parameters in the photo-active blend (P3HT:PCBM). The performance of OSCs improved when the active layer was cast from the chlorobenzene solution rather than 1,2-dichlorobenzene solution. Varying the blend ratio also revealed improved device performance with the 1:0.6 weight ratio. All these parameter processes can significantly influence the device performance. The effects of ZnO particle morphology on the performance of OSC devices were investigated. The best photovoltaic properties were obtained from devices with the ZnO nanoflakes and nanoparticles as electron extraction layers both spin coated from solutions of 0.5 mg/mL ZnO concentration. The ZnO nanoflakes morphology gave relatively higher power conversion efficiency (PCE) of 3.08 % versus 2.37 % from the ZnO nanoparticles. The effects of thermal treatment before (pre annealing) and after (post-annealing) the deposition of Al electrode on the conventional devices were also investigated. Improved photovoltaic properties were observed from the post-fabrication annealed device. The inverted device with ZnO nanoparticles electron extraction layer revealed a relatively improved performance versus that with ZnO nanoflowers. Finally the compositional depth profiling and surface imaging were carried out for both conventional and inverted devices and the results indicated that the bulk heterojunction (BHJ) layer was P3HT enriched and there was diffusion of some other elements into the BHJ layer. The surface imaging showed homogeneous as well as inhomogeneous distribution of ions on the surface.
Thesis (Ph.D. (Physics))--University of the Free State, 2013
Keywords: Zinc oxide; Organic solar cells; Photovoltaics; Morphology; Power conversion efficiency; Nanoparticles; Solar cells